Analisis kesulitan siswa dalam mengerjakan soal matematika pada materi fungsi komposisi dan fungsi invers ditinjau dari motivasi belajar - Yulianti, Euis Nopi; Rahmawati, Noviana Dini; Purwosetiyono, FX Didik (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study aims to analyze the difficulties of students in working on math problems on the composition function and inverse function material in terms of high student learning motivation, analyze students' difficulties in working on math problems on the composition function and inverse function material in terms of moderate student learning motivation, to analyze students' difficulties. in doing math problems on the material of composition function and inverse function in terms of low student motivation. The subjects of this research were students of class XII of SMK Fatahilah Cipari, totaling 32 students. Data collection techniques using questionnaires, written tests, interviews and documentation. The results showed that: 1) Students who had high motivation, tended to have a little difficulty and it could be seen from the results of the work on questions 1A and 1B that students' answers were correct, only on question 1B students were less precise in giving conclusions at the end of answers 2) Students who had moderate motivation, tends to have difficulty and can be seen from the results of the answers 1A students do not give conclusions and 1B students do not understand the concept and apply principles 3) Students who have low motivation tend to have difficulties and can be seen from the answers of students 1A and 1B do not understand the concept, apply principles and difficulties in solving verbal problems.